2001
DOI: 10.1111/j.1151-2916.2001.tb00960.x
|View full text |Cite
|
Sign up to set email alerts
|

Crack‐Healing Behavior Under Stress of Mullite/Silicon Carbide Ceramics and the Resultant Fatigue Strength

Abstract: Mullite/SiC composite ceramics were sintered and subjected to three-point bending of specimens made according to the appropriate JIS standard. A semicircular surface crack 100 to 250 m in diameter was made on each specimen. We systematically studied crack-healing behavior and cyclic-and staticfatigue strengths at room temperature and 1000°C (crackhealing temperature) by using three types of specimens (smooth, cracked, and crack-healed). The main conclusions are as follows: (i) mullite/SiC composite ceramics ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 18 publications
1
66
1
Order By: Relevance
“…Microcracks in crystalline SiO 2 (quartz) with a length of 100 µm and a width of 10 µm were completely healed by exposure to a water pressure of 200 MPa at 600 ℃ for 4 h [50]. Strength recovery by hightemperature oxidation induced crack healing with environmental oxygen at elevated temperatures was reported from a number of non-oxide ceramics as well as oxide ceramics loaded with SiC [26,30,34,[39][40][41]51,[69][70][71][72][73][74]. For example, annealing of SiC reinforced Al 2 O 3 nanocomposites in inert Ar atmosphere resulted in a strength increase of 50% relative to the unannealed specimen whereas annealing in air yielded a three-fold improvement in the indendation strength [69].…”
Section: Oxidation Reaction Crack Healingmentioning
confidence: 97%
“…Microcracks in crystalline SiO 2 (quartz) with a length of 100 µm and a width of 10 µm were completely healed by exposure to a water pressure of 200 MPa at 600 ℃ for 4 h [50]. Strength recovery by hightemperature oxidation induced crack healing with environmental oxygen at elevated temperatures was reported from a number of non-oxide ceramics as well as oxide ceramics loaded with SiC [26,30,34,[39][40][41]51,[69][70][71][72][73][74]. For example, annealing of SiC reinforced Al 2 O 3 nanocomposites in inert Ar atmosphere resulted in a strength increase of 50% relative to the unannealed specimen whereas annealing in air yielded a three-fold improvement in the indendation strength [69].…”
Section: Oxidation Reaction Crack Healingmentioning
confidence: 97%
“…where Dmullite, DSiC, Dalumina, and Dsilica are the theoretical densities of mullite (3.160 g/cm 3 ), SiC (3.218 g/cm 3 ), Al2O3 (3.987 g/ cm 3 ), and cristobalite (2.330 g/cm 3 ), and Vmullite, VSiC, Valumina, and Vsilica are the volume fractions of mullite, SiC, Al2O3, and cristobalite, respectively. Vmullite, VSiC, Valumina, and Vsilica can simply be calculated from both the weight change of the specimen in the sintering process and the weight change of each SiC powder when oxidized under the same conditions.…”
Section: Jcs-japanmentioning
confidence: 99%
“…2) Ando et al 3) reported that mullite-SiC composites have the ability to heal semicircular cracks having diameters of up to 200 μ m.…”
Section: Introductionmentioning
confidence: 99%
“…Since mullite has low fracture toughness and low bending strength, incorporation of nano-sized second-phase particles, such as SiC, into the mullite matrix could improve its mechanical properties. Ando et al 12) and Takahashi et al 13) also showed that mullite-SiC composites exhibited self-healing characteristics.…”
Section: Introductionmentioning
confidence: 99%